Klientelisme sebagai Perilaku Koruptif dan Demokrasi Banal - Ramadhan, Muhammad Nur; Oley, Jimmy Daniel Berlianto (Integritas : Jurnal Antikorupsi, 2019)
Clientelism or clientelist practices is still a part of Indonesia’s democracy, especially regarding electoral and local practices. Seeing clientelism as a corruptive behavior goes deep into its meaning, which is a two-way transaction, therefore in need of two-sided elucidation: supply and demand part. In this context, the demand that is continuously found in democratic practices is a logical consequence of the capacity lack of voters or citizen to control their representative and political figures. Especially to ensure that their welfare is a part of the political agenda. Specifically, there are two factors identified that make clientelism a logical consequence, which is unfulfilled rights as a citizen and the malfunctioning of political representation. Therefore, to respond to these corruptive and distortive phenomena, there are at least four strategies to implement. First, tighten and have more rigorous post-election programs implementation. Second, provide a local and socially-rooted mechanism and platform to control political figures. Third, reforming regulations on the patron-client relationship, especially in political/electoral momentum. Lastly, tighten the supervision of recess activities. Keywords: Clientelism, Democracy, Well-Being, Corruptive Behavior, Recess